Optical coherence tomography (OCT) to image active and inactive retinoblastomas as well as retinomas. Issue 2 (26th August 2019) - Nadiarnykh, Oleg; McNeill‐Badalova, Nuray A.; Gaillard, Marie‐Claire; Bosscha, Machteld I.; Fabius, Armida W.M.; Verbraak, Frank D.; Munier, Francis L.; de Boer, Johannes F.; Moll, Annette C.
Abstract: Purpose: To illustrate Optical Coherence Tomography (OCT) images of active and inactive retinoblastoma (Rb) tumours. Methods: Current observational study included patients diagnosed with retinoblastoma and retinoma who were presented at Amsterdam UMC and Jules‐Gonin Eye Hospital, between November 2010 and October 2017. Patients aged between 0 and 4 years were imaged under general anaesthesia with handheld OCT in supine position. Patients older than 4 years were imaged with the conventional OCT (Heidelberg Engineering, Heidelberg Spectralis, Germany). All patients included were divided into two groups: active and inactive tumours (retinoma and regression patterns). Patients' medical records and OCT images were analysed during meetings via discussions by ophthalmologists and physicists. Results: Twelve Dutch and 8 Swiss patients were divided into two groups: 2 patients with active tumour versus 18 patients with inactive tumour. Subsequently, inactive group could be divided in two groups, which consisted of 10 patients with retinoma and 8 patients with different regression pattern types. Of all included patients, 15 were male (75%). Median age at diagnosis was 18.0 months (range 0.19–715.2 months). A total of 12 retinoblastoma (active and inactive) and 8 retinoma foci were investigated by OCT. No distinction could be made between active and inactive tumours using only OCT. Conclusion: Optical coherence tomography alone cannot distinguish between active and inactive Rbs. However, handheld OCT adds useful information to the established imaging techniques in the monitoring and follow‐up of retinoblastoma patients. With this study, we provide an overview of OCT images of active and inactive Rbs.